P068 Assessing the Effectiveness of an Educational Series on Prior Authorization of IBD Treatments. (December 2019) - Faler, Whitney; Perez, Jan; Tordoff, Sharon; Gross, Tara; Salinas, Greg
Abstract : BACKGROUND: Prior authorization (PA) poses a burden to HCPs and their staffs when prescribing biologic therapy for patients with IBD. Our aim was to determine the effectiveness of 3 CME activities on clinician knowledge, confidence, and performance related to PA processes and success rates for biologic therapy. METHODS: Outcomes measurements were taken directly before (n ≥ 241) and after the activities (n ≥ 229), as well as 3-months after activity completion. This 3-month follow-up sample (n = 30) was matched at the same time to a control sample of clinicians who did not participate in the education (n = 30). RESULTS: 4, 840 learners completed the 3 modules, including 1, 195 downloads of the podcast version. Key knowledge improvements were shown in helping patients with medication co-pays, use of specialty pharmacists, standardizing EHR clinical documentation of patients with IBD, requesting peer-to-peer review, and expediting submissions with the use of templates. Prior to participation, confidence in the current processes to manage prior authorizations was low. Three months following education, nearly all clinicians surveyed indicated that they were "confident" or "extremely confident" in these elements of care. Comparative analysis shows a large effect when comparing the educational learners pre- vs. post-activity (Cohen's d = 1.37) and pre- vs. 3 –month follow-up (d = 0.55). However, comparing post-participation vs. a non-participant control is smaller (d = 0.20, 15%). This shows that our particular educational learners were coming at this program with more knowledge and practice gaps in the pre-authorization process than the general clinician population. Predictive modeling utilized a regression analysis showed increasing confidence in the use of AGA Care Pathways will significantly increase documentation of pertinent lab results and imaging related to IBD and significantly increase use of a template. CONCLUSION(S): This program achieved large reach with education targeted specifically to those clinicians who needed it most. The education increase clinician knowledge and confidence in the use of this knowledge to acquire prior authorization for biologics. For future PA initiatives, learners may benefit from a mock review of a PA request to best explain individual elements of the decision-making process.